Sense and sensitivity : essays on reading the Bible in memory of Robert Carroll - Carroll, Robert P.; Davies, Philip R.; Hunter, Alastair G. (Journal for the study of the Old Testament. Supplement series ;, 2002)
In this collection of studies to the memory of Robert Carroll, and reflecting his interests in prophecy, ideology and reception history, are contributions from Graeme Auld, John Ashton, Alice Bach, Hans Barstad, Joseph Blenkinsopp, Athalya Brenner, David Clines, Johann Cook, Robert Davidson, Philip Davies, Sean Freyne, Norman Gottwald, Lester Grabbe, John Halligan, Alastair Hunter, David Jasper, William Johnstone, Gabriel Josipovici, Francis Landy, Heather McKay, Stephen Prickett, Hugh Pyper, Stefan Reif, John Sawyer, Robert Setio, Yvonne Sherwood, Carol Smith and Johanna Stiebert.